Two hands, one brain, and aging. (April 2017) - Maes, Celine; Gooijers, Jolien; Orban de Xivry, Jean-Jacques; Swinnen, Stephan P.; Boisgontier, Matthieu P.
Highlights: Aging makes bimanual coordination performance more cognition-dependent. Hyper and hypo-activity in the aging brain may interact to determine performance. Higher resting-state connectivity is associated with lower performance in olders. Task-related connectivity increases with higher task demand irrespective of age. Abstract: Many activities of daily living require moving both hands in an organized manner in space and time. Therefore, understanding the impact of aging on bimanual coordination is essential for prolonging functional independence and well-being in older adults. Here we investigated the behavioral and neural determinants of bimanual coordination in aging. The studies surveyed in this review reveal that aging is associated with cortical hyper-activity (but also subcortical hypo-activity) during performance of bimanual tasks. In addition to changes in activation in local areas, the interaction between distributed brain areas also exhibits age-related effects, i.e., functional connectivity is increased in the resting brain as well as during task performance. The mechanisms and triggers underlying these functional activation and connectivity changes remain to be investigated. This requires further research investment into the detailed study of interactions between brain structure, function and connectivity. This will also provide the foundation for interventional research programs towards preservation of brain health and behavioral performance by maximizing neuroplasticity potential in older adults.